USING APPRECIATIVE INQUIRY (AI) TO EVALUATE AN EDUCATION SUPPORT NGO IN SOWETO - Fynn, Angelo (PINS-Psychology in Society, 2025)
The purpose of this paper is to discuss the application of the Appreciative Inquiry (AI) approach while evaluating an emerging Non Governmental Organisation (NGO) in Soweto, South Africa. The AI approach was originally introduced as an organisational development tool intended to shift the focus from deficit-based evaluation to an appreciative stance that considered the organisation when it functioned at its peak. The use of this approach was motivated by the belief that it would provide emerging NGOs with an acknowledged method of implementing their development agendas in the face of donor or governmental organisational resistance. While the AI approach intends to provide a broad platform for stakeholder interaction, the experience of this study was that it requires a significant amount of political resources to include stakeholders from outside the organisation to participate actively. Our experience of the AI approach was that it seems to be difficult to implement in an environment where there are low levels of trust and cohesion among the stakeholders. The paper concludes with suggestions for researchers, especially novice researchers, entering the field with the intention of utilising AI in the Soweto context.